Social Development Model : Poverty Alleviation Based on Spirituality - Nurdin, Muhamad Fadhil (Sosioglobal, 2016)
This article is a model of social development for poverty alleviation based on spirituality. Social development requires thinking that is consistent between the conception and the practice. Social development activities is a business that is relentless, as long as there is still the problem of human life and require completion. Focus on building human with the goal of allowing people to enjoy life in a creative, healthy and prosperous. It is expected become constructive model for the governments poverty alleviation. This article is based on qualitative research and content analysis. All data were obtained from literature sources, official documents, books, journals and newspapers. The findings have been integrating the concept of mans spiritual well-being into a social development model for poverty alleviation in Indonesia. In particular, the proposed model is an alternative model to incorporate some of the positive elements of the western paradigm and spiritual aspects, especially from the perspective of Islam. The proposed model was developed based on the creativity in the establishment of a comprehensive social policy.